Panel Discussion In Honor of Dr Tom Waters The NIOSH Lifting Equation - Part II: Exploring Proposed Extensions and Beyond. (September 2016) - Fox, Robert R.; Maikala, Rammohan V.; Occhipinti, Enrico; Colombini, Daniela; Alvarez-Casado, Enrique; Gallagher, Sean
With the introduction of the NIOSH Lifting Equation, specifically after the publication of the Revised Lifting Equation (RLE) (Waters et al., 1993), occupational health and safety professionals across the world have successfully utilized the RLE to evaluate the risks associated with lifting and lowering tasks in the workplace. Although the RLE takes into consideration of various job task variables to determine recommended weight limits for a variety of task combinations, a number of articles and peer reviewed publications have appeared with a notion of either extending or modifying the RLE to address manual handling situations that the original equation was not able to assess comprehensively. The purpose of this panel discussion will be to provide an overview to ergonomics practitioners and researchers of these extensions and beyond, thus exploiting the full potential of this lifting equation. The first presentation will discuss the Variable Lift Index (VLI) for highly variable manual lifting tasks, whereas the second presentation describes the Sequential Lift Index (SLI) in assessing a sequence of lifting tasks that workers perform while they rotate to different tasks over a workday. In addition to the inherent variability in lifting tasks assumed by the RLE, we often encounter materials handling scenarios associated with one-handed lifting, team lifting, lifting of people (e.g., patient handling), lifting while seated or kneeling, lifting on improper frictional surfaces, lifting unstable loads, or lifting for more than 8 hours. To this effect, the third presentation examines the wider application of the RLE by adding new multipliers to the equation. Extending further on quantifying typical lifting task-related variables and associated risk on the lower back, the final presentation explores the fatigue failure process experienced by the lumbar spine when performing multiple and varied lifting tasks. This innovative approach is nascent in ergonomics literature, especially in ergonomics risk assessment, and has great potential in injury prevention at the workplace.